Gastric Glomic Tumor: A rare case of benign neoplasm (Research, Society and Development, 2023)
Gastric glomus tumor is a neoplastic lesion originating in the neuromyoarterial canal. The usual location of the glomus body allows the incidence of this type of tumor to occur, most of the time, in peripheral soft tissues and extremities. However, glomus tumors may rarely develop in visceral regions such as the gastrointestinal tract. In this sense, there are also rare reports in the scientific literature on this type of neoplasm, which makes identification even more difficult before surgical intervention. Some strategies have been used in recent decades to make diagnosis more efficient, among which computed tomography (CT) stands out. This case report conducted a systematic review of the scientific literature to theoretically substantiate a case report. For the development of this study, we report a case of a male patient, 54 years old, with a history of hematochezia for approximately 2 months. The patient underwent a series of analyzes to detect the type of gastric tumor. Among these exams that were used in the diagnosis, CT was responsible for the unequivocal detection of the gastric glomus tumor, since the tumor was well-defined by contrast. The main objective of the present study is to help in the differential diagnosis in cases of hematochezia, as well as in the differentiation of gastric glomus tumors from other gastrointestinal stromal tumors.